Analysis of Unlawful Credit Card Collection Practices by Debt Collectors in Semarang - Indra Adi Saputra (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
This study analyzes unlawful credit card collection practices by debt collectors in Semarang and identifies legal protection mechanisms available for debtors. The research addresses the gap between existing regulatory frameworks and field practices, as evidenced by 17,849 complaints recorded between 2024 and 2025 regarding debt collector violations. Using a qualitative descriptive method with a case study approach, this research references OJK regulations (POJK No. 22/2023, SEOJK No. 15/2018), the Consumer Protection Law (No. 8/1999), and empirical data from media reports and official documents. The findings reveal that illegal collection practices include verbal threats, intimidation, calls outside permitted hours, and unauthorized dissemination of personal data, causing psychological, social, and financial harm to debtors. Legal protection mechanisms available include complaints to OJK, BPSK dispute resolution, civil lawsuits under Article 1365 of the Indonesian Civil Code, and criminal reports to the police. The study concludes that consistent law enforcement, regulatory supervision, and legal literacy are essential to prevent unlawful practices. Persuasive and digital collection approaches have proven effective in reducing violations and increasing compliance, serving as a reference for academics, legal practitioners, financial institutions, and the public to enhance consumer protection and ensure fair debt collection practices.